Influence of organic, mineral fertilizers and their combination on the Renewing Power of Macabo in Kisangani, DR Congo - F, Ramazani; F, A.Ngama; L, Okungo A. (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
In order to help solve the thorny problem of low availability and propagation rate in Macabo (Xanthosoma sagittifolia (L.) Schott.), given that a planted cutting yields only one plant for a new plantation after cultivation and harvesting, a study was carried out in Kisangani using two types of manure. It consisted in assessing the effect of organic manure (pig dung and decomposed cow dung) and mineral manure (NPK), as well as their combination, on Macabo's capacity to produce ex-situ rejections.The parameters studied were, respectively, the recovery rate of the mother cuttings and the number of shoots produced during the first eight weanings. The results showed that: (1) The recovery rate of mother cuttings was 100% whatever the treatment; (2) After eight weanings, the organic and mineral manure combinations produced more shoots, with an average of 32 and 30 respectively for T4 (pig dung + mineral manure) and T5 (cow dung + mineral manure). These results indicate that the number of offspring produced does indeed depend on the manures used; (3) The average number of offshoots per plant decreased during weaning for all treatments; The results suggest that this technique can be advantageously used to produce quality planting material for this crop in quantity and in a short time.